Population survey of Peary caribou (Rangifer tarandus pearyi) and muskoxen (Ovibos moschatus) on Banks Island, Northwest Territories, July 2010 - Davison, Tracy; Pongracz, Jodie; Williams, Judy (Rangifer, 2013)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false SV X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> We conducted a systematic aerial transect survey of Peary caribou (Rangifer tarandus pearyi) and muskoxen (Ovibus moschatus) on Banks Island, Northwest Territories, in July 2010. The population estimate of adult Peary caribou was 1097 ± 343 (95% Confidence Interval: CI), which is not significantly different from the 2005 estimate of 929 ± 289 (95% CI; P < 0.05). The current number, however, is a 4- to 9-fold decrease since the 1980s. The adult muskoxen population estimate was 36 676 ± 4031 (95% CI), which is significantly lower than the 2005 estimate of 47 209 ± 3997 (95% CI; P < 0.05).